L’esthétique Théâtrale De L’objet Récupéré : De La Matérialité Quotidienne À La Représentation Scénique - Khalid, Tadili (European Scientific Journal, ESJ, 2018)
This paper focuses on highlighting the particular contribution of the recovered object in the change of artistic techniques and the aesthetic modalities of theatrical representation. It is an opportunity to emphasize this alliance between everyday materiality and the space of the scenic representation in the form of the recovery of the forgotten and an attribution of a second life which is relative to objects marked by obsolescence. Objects loaded from reality, familiar use, and social sharing acquired rhetorical functioning captivated by their use in unusual space. Our approach consists of stopping on this particularity of the recovered object from a comparative study of its different uses by the directors and the playwrights. This is done in order to highlight the artistic potentialities which it generates and the various aesthetic reports that it triggers in the theatrical field. This type of representation highlights the fight against the obsolescence in favor of a new spectacular load so as to mobilize the spectators' imagination. For this purpose, it seems to us that the recovered object is able to find the base of its aesthetic representation. It is about a reflection object which makes the usual the origin of a rhetorical expressivity in order to place it at the very center of the theatrical creation.